2009
DOI: 10.1002/syn.20710
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the environment on the dendritic morphology of the rat auditory cortex

Abstract: The present study aimed to identify morphological correlates of environment-induced changes at excitatory synapses of the primary auditory cortex (A1). We used the Golgi-Cox stain technique to compare pyramidal cells dendritic properties of Sprague-Dawley rats exposed to different environmental manipulations.Sholl analysis, dendritic length measures, and spine density counts were used to monitor the effects of sensory deafness and an auditory version of environmental enrichment (EE). We found that deafness dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 60 publications
5
65
1
2
Order By: Relevance
“…The functional significance of this change is unclear, although it is likely to alter the integrative properties of the neurons. It is, however, interesting that secondary dendrites may show more activity-dependent morphological plasticity than primary dendrites (Charych et al, 2006;Horton et al, 2007), and that basal and apical dendrites differ in their activity-dependent plasticity (Cook et al, 2004;Brown et al, 2005;Bose et al, 2010). The levels of RhoB in the rat and mouse CNS are high from around embryonic day 16 to birth, and then decrease slightly postnatally (Olenik et al, 1999;Komagome et al, 2000;Yoon et al, 2007).…”
Section: Rhobmentioning
confidence: 99%
“…The functional significance of this change is unclear, although it is likely to alter the integrative properties of the neurons. It is, however, interesting that secondary dendrites may show more activity-dependent morphological plasticity than primary dendrites (Charych et al, 2006;Horton et al, 2007), and that basal and apical dendrites differ in their activity-dependent plasticity (Cook et al, 2004;Brown et al, 2005;Bose et al, 2010). The levels of RhoB in the rat and mouse CNS are high from around embryonic day 16 to birth, and then decrease slightly postnatally (Olenik et al, 1999;Komagome et al, 2000;Yoon et al, 2007).…”
Section: Rhobmentioning
confidence: 99%
“…Dendrites regulate the integration of inputs and provide sites for synapses on spines (41, 42). As such, they are extremely plastic structures that undergo changes in response to experience, which is especially evident during development (12,(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57). For this reason, a delay in the formation of dendritic trees in the prefrontal cortex may be important for processing and integrating the extensive load of information that both humans and chimpanzees acquire during development and for maintaining plasticity of executive functions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animal studies have shown that brain development relies on developmentally appropriate acoustic stimulation early in life (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Auditory deprivation during critical periods can adversely affect brain maturation and lead to long-lasting neural despecialization in the auditory cortex (AC), whereas auditory enrichment in the early postnatal period can enhance neural sensitivity in the primary AC, as well as improve auditory recognition and discrimination abilities.…”
mentioning
confidence: 99%